Development of Tracking System for Motorcycle - Che Othman, Muhamad Rizuwan Aizat; Zarina Tukiran (Evolution in Electrical and Electronic Engineering, 2024)
This paper discusses the development of a tracking system by utilizing the Internet of Things (IoT) and Global Positioning System (GPS) technologies to assist motorcycle users to locate their vehicles. The system comprises a tracker device and a cloud-based database. The tracker device obtained location information of latitude and longitude and transmitted the information to the Firebase real-time database. The tracker device comprises a NodeMCU ESP8266 and a GPS module. Based on the experiments conducted, the tracking system is able to locate the device with an accuracy of ±50 meters. The tracking system also had a long battery life, capable of withstanding 90 hours of use.